The silent wife eaudiobook - Slaughter, Karin (Will Trent, 2020)
WATCH WILL TRENT ON ABC! The New York Times bestselling author of Pieces of Her returns with the next novel in the Will Trent series that "comes with just the right amount of twists, turns, shocks, surprises and domestic thrill and shrill" (Parade). He watches. He waits. He takes. Who will be next . . . Atlanta, Georgia. Present day. A young woman is brutally attacked and left for dead. The police investigate but the trail goes cold. Until a chance assignment takes GBI investigator Will Trent to the state penitentiary, and to a prisoner who says he recognizes the MO. The attack looks identical to the one he was accused of eight years earlier. The prisoner's always insisted that he was innocent, and now he's sure he has proof. The killer is still out there. As Will digs into both crimes it becomes clear that he must solve the original case in order to reach the truth. Yet nearly a decade has passed—time for memories to fade, witnesses to vanish, evidence to disappear. And now he needs medical examiner Sara Linton to help him hunt down a ruthless murderer. But when the past and present collide, everything Will values is at stake ...]